Human amnion mesenchymal cells are pro-inflammatory when activated by the Toll-like receptor 2/6 ligand, macrophage-activating lipoprotein-2. (August 2016) - Sato, Brittany L.; Collier, Eric S.; Vermudez, Sheryl Anne; Junker, Anthony D.; Kendal-Wright, Claire E.
Abstract: Introduction: Infection accounts for over 40% of preterm premature rupture of the fetal membranes (PPROM), a major cause of preterm birth. Toll-like receptors (TLR) play key roles in pathogen surveillance but their expression and function in amnion mesenchymal cells (AMC) is unclear. The aims of this study were to determine the expression of all TLR isoforms and the effect of macrophage-activating lipoprotein-2 (MALP-2), derived from a common pathogen involved in PPROM, on human AMC. Methods: AMC were isolated from normal, term amnion from repeat cesarean section. Semi-quantitative RT-PCR, immunocytochemistry, immunohistochemistry and western blotting were used to detect TLR isoform expression. Immunocytochemistry of NF-κB p65, pro-inflammatory cytokine secretion (ELISA), MTT assay, LDH assay, immunoblotting of cytosolic cytochrome c and cleaved caspase-3, and expression of 84 microRNAs by Qiagen miRNA PCR array were used to determine the functional effect of MALP-2 on AMC. Results: TLR1-10 was detected in AMC, and protein expression of TLR2, 4, and 6 were confirmed. MALP-2 induced nuclear translocation of p65, reaching significance after 45 min (ANOVA, P < 0.05). MALP-2 did not cause apoptosis but did lead to significant secretion of IL-4, IL-6, and IL-8 ( P < 0.05, 0.01, 0.001, respectively) and significant changes in miRNA-320a and miRNA-18a ( P < 0.05). Discussion: These results suggest that AMC elicit a pro-inflammatory response following stimulation with the known TLR2/6 ligand MALP-2. This data supports the idea that AMC express the innate immune system receptors that could help with immune surveillance during infection and contribute to inflammatory responses that lead to PPROM. Highlights: Expression of TLR1-10 isoforms was confirmed in human amnion mesenchymal cells. MALP-2 induced TLR2/6-mediated NF-kB signaling. MALP-2 was pro-inflammatory in AMC, but not apoptotic. MicroRNA-320a and 18a expressions in AMC were significantly altered by MALP-2.